CITATIONS OR JOURNAL QUALITY: WHICH IS REWARDED MORE IN THE ACADEMIC LABOR MARKET?. (2nd May 2017) - Gibson, John; Anderson, David L.; Tressler, John
Abstract : Research quality can be evaluated from citations or from the prestige of journals publishing the research. We relate salary of tenured University of California (UC) economists to their lifetime publications of 5, 500 articles and to the 140, 000 citations to these articles. Citations hardly affect salary, especially in top‐ranked UC departments where impacts of citations are less than one‐tenth those of journals. In lower ranked departments, and when journal quality is less comprehensively measured, effects of citations on salary increase. If journal quality is just measured by counting articles in journal tiers, apparent effects of citations are overstated. ( JEL A14, J44)